2016
DOI: 10.1007/s10596-016-9579-y
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of mean-field homogenisation methods for predicting shale elastic response

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The capabilities of homogenisation techniques in shales was investigated using numerical simulations in which several virtual shale microstructures were generated and studied (Goodarzi et al . ). Good agreement was obtained between the macroscopic elastic responses of the numerical rocks and the predicted values from the homogenisation methods.…”
Section: Implementation Of Multi‐scale Homogenisation Techniquesmentioning
confidence: 97%
See 3 more Smart Citations
“…The capabilities of homogenisation techniques in shales was investigated using numerical simulations in which several virtual shale microstructures were generated and studied (Goodarzi et al . ). Good agreement was obtained between the macroscopic elastic responses of the numerical rocks and the predicted values from the homogenisation methods.…”
Section: Implementation Of Multi‐scale Homogenisation Techniquesmentioning
confidence: 97%
“…As was highlighted in Section , numerical studies using SCS and MT schemes for predicting homogenised elastic response of matrix‐inclusion morphology showed that each of this elastic constant can be better predicted with one of these schemes (Goodarzi et al . ). In fact, the error observed in homogenised stiffness tensor components can be seen as the combined error of homogenised elastic constants.…”
Section: Implementation Of Multi‐scale Homogenisation Techniquesmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, the same rock sample can be examined under varying testing conditions or mineral composition, which can be virtually varied [ 48 ]. Present numerical models employ calculation techniques to determine static [ 49 , 50 , 51 ] and dynamic moduli [ 52 ] mainly for reservoir rocks such as sandstones [ 53 , 54 ] and carbonates [ 55 , 56 ], but also for shales [ 57 ]. However, there is still a discrepancy between the achieved numerical estimates of mechanical properties derived from micro-CT images and laboratory data, where, regardless of the numerical approach, the simulated moduli are systematically higher [ 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%